Virtual Communication in the Program Supervisor Coaching 1-on-1 Rumah Kepemimpinan Scholarship Participants (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The existence of virtual communication using the internet affects all sectors of society, including education and impact coaching. Virtual communication in the Supervisor Coaching 1-on-1 program conducted by Rumah Kepemimpinan facilitates each participant to enjoy greater flexibility in the process of self-development, where Supervisors dig deeper into the challenges, needs, aspirations of each participant, then discuss problems or obstacles that arise in order to support participants to become the best version of themselves. This research uses a qualitative conceptual model of Computer Mediated Communication with the aim to describe the interaction and engagement (active participation and openness) and the use of the teleconferencing platform (challenges, benefits, and constraints) with analysis leading to a higher level of abstraction; from manifest content to latent content. Data was collected from semi-structured interviews via Zoom Meeting teleconference to 4 participants and 3 Supervisors who had undergone 1-on-1 Supervisor Coaching for 14 months. The results showed that the interaction and active participation of participants with Supervisors in the use of the teleconference platform resulted in effective outcomes to help participants improve themselves, overcome challenges, and be more open in achieving goals. However, obstacles such as signal and internet networks are still a problem.
Keywords: Coaching 1-on-1; Computer mediated communication; Supervisor; Virtual communication